2008
DOI: 10.1016/j.bbadis.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential metabolic consequences of fumarate hydratase and respiratory chain defects

Abstract: Defects of the oxidative ATP production pathway lead to an amazing variety of disease phenotypes, ranging from childhood encephalomyopathies to hereditary tumor formation. A key enzyme of tricarboxylic cycle, fumarate hydratase (FH), is involved in encephalopathies, but also in leiomyoma formation, and occasionally also in various types of cancer. MELAS (mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes) and NARP (neuropathy ataxia retinitis pigmentosa) are progressive neurological diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…The FH-specific networks identified in primary fibroblasts were then tested in FH-deficient leiomyoma transcriptome data sets, to study the relevance of fibroblast data to leiomyoma formation. Although FH-deficient fibroblasts were diploid with normal growth behavior (Raimundo et al, 2008), but showed low FH activity similar as FH-deficient leiomyomas, networks common to these cells and leiomyomas are excellent candidates to be involved in FHrelated leiomyoma formation. We show here that FHdeficient fibroblasts and leiomyomas show widespread downregulation of the SRF-regulated transcripts and also of active SRF, known to participate in smooth muscle cell differentiation (Pipes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The FH-specific networks identified in primary fibroblasts were then tested in FH-deficient leiomyoma transcriptome data sets, to study the relevance of fibroblast data to leiomyoma formation. Although FH-deficient fibroblasts were diploid with normal growth behavior (Raimundo et al, 2008), but showed low FH activity similar as FH-deficient leiomyomas, networks common to these cells and leiomyomas are excellent candidates to be involved in FHrelated leiomyoma formation. We show here that FHdeficient fibroblasts and leiomyomas show widespread downregulation of the SRF-regulated transcripts and also of active SRF, known to participate in smooth muscle cell differentiation (Pipes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The patient cell lines have been described in detail in Raimundo et al (2008). In short, four FH-deficient fibroblast lines from patients with recessive FH deficiency were used-FH-1, homozygous for the E362Q mutation (Bourgeron et al, 1994); FH-2, homozygous for the Q376P mutation (Remes et al, 2004); FH-3 is a compound heterozygote with InsK477/ R233H (Loeffen et al, 2005); and FH-4 is a compound heterozygote with delV387 and Q386H changes in one allele, and P369S in the other (Maradin et al, 2006).…”
Section: Cellsmentioning
confidence: 99%
See 3 more Smart Citations